190k views
1 vote
Solve(x+y)^2=(x^2-2xy+y^2) and show your work

User Exan
by
5.6k points

2 Answers

4 votes

The answer is 0!

Hope i helped :)

User Lebecca
by
5.6k points
4 votes

(x + y)^2 = (x^2 - 2xy + y^2)

First distribute the ^2 on the left side of the equation to each term inside the parenthesis:

x^2+ 2xy + y^2

Now pick one of the variables to solve for and isolate it:

(solving for x)

x^2 + 2xy + y^2 = x^2 - 2xy + y^2

x^2+ 2xy = x^2 - 2xy

2xy = -2xy

-x = x

x = 0

When you solve for y in the equation it will turn out to be 0 as well

User Firatozcevahir
by
6.5k points